Innovative epilepsy management: a combined figure of EEG categorization and medication mechanisms - Mohamed Taha; Douglas R. Nordli; Carol Park; Douglas R. Nordli (Frontiers in Neurology)
IntroductionEpilepsy management requires precision in diagnosis and treatment, particularly when selecting antiseizure medications based on specific epilepsy syndromes. We present an innovative educational tool that integrates EEG categorization with antiseizure medication mechanisms, designed to enhance clinical decision-making in epilepsy management.MethodsThis study evaluated a cohort of neurology trainees through a pre-test and post-test design. Participants were assessed on their ability to diagnose epilepsy syndromes and select appropriate treatments based on EEG findings before and after exposure to the teaching figure. The figure aligns key EEG patterns with specific epilepsy syndromes and outlines the corresponding mechanisms of action of antiseizure medications.ResultsPost-test results demonstrated a statistically significant improvement in trainees’ ability to analyze clinical cases and make informed treatment decisions (mean pre-test score: 52.8; post-test score: 66.5; p = 0.0019). The figure facilitated a deeper understanding of the relationship between EEG findings and medication selection, particularly in complex cases.DiscussionThe integration of EEG patterns with antiseizure medication mechanisms allows for more precise epilepsy syndrome diagnosis and enhances the selection of rational polypharmacy approaches. This approach not only improves educational outcomes but also offers potential applications in clinical practice for personalized epilepsy treatment strategies.ConclusionThis innovative figure bridges the gap between EEG categorization and treatment strategies, providing a valuable tool for improving epilepsy management education and clinical outcomes.Plain language summaryThis manuscript introduces a teaching tool that helps providers better understand how brainwave patterns (EEGs) relate to epilepsy types and guides them in choosing the most effective seizure medications.